DIABETES MELLITUS IN PATIENTS WITH LIVER CIRRHOSIS: NEW TREATMENT OPTIONS - L. Yu. Morgunov (Исследования и практика в медицине, 2017)
In economically developed countries, cirrhosis is one of the six leading causes of death at the age of 35–60 years and ranges from 14 to 30 cases per 100000 population. In the world 40 million people die of cirrhosis each year. At 6% of the population of the Russian Federation there is a diabetes mellitus. The combination of diabetes mellitus in patients with cirrhosis of the liver is a common comorbid pathology. Diabetes mellitusis a risk factor for the development of liver cirrhosis, and the incidence of combination of both diseases is quite high, although the frequency of occurrence varies. About 80% of patients with LC may have impaired glucose metabolism, and 30% have diabetes mellitus. Prospective studies have shown that diabetes is associated with an increased risk of developing hepatic complications and death in patients with cirrhosis of the liver. Diabetes mellitus increases the risk of complications of liver cirrhosis of any etiology (varicose veins of the esophagus, hepatic encephalopathy, hepatic-cell insufficiency) and subsequent survival. The incidence, frequency of hospitalizations and mortality from this combined pathology are very high. There are common mechanisms that provoke metabolic and autoimmune disorders in the development of chronic hepatitis and cirrhosis, leading to steatosis, insulin resistance, impaired glucose tolerance and the development of diabetes mellitus. There are certain features of the evaluation of the compensation of carbohydrate metabolism in patients with cirrhosis of the liver, anemia and impaired protein metabolism. Effective control of glycemia can have a beneficial effect on the treatment of these patients. However, few studies have evaluated the efficacy and safety of antidiabetic drugs and the effect of diabetes treatment on morbidity and mortality in patients with cirrhosis. Previously it was believed that in the presence of cirrhosis the only treatment remains insulin. At present, in connection with the emergence of modern groups of hypoglycemic drugs, as well as new approaches to the treatment of type 2 diabetes, this concept has radically changed. Unfortunately, the issues of correction of carbohydrate metabolism in patients with cirrhosis of the liver are practically not covered in the world literature. This article deals with the correction of carbohydrate metabolism in patients with cirrhosis and hepatocellular insufficiency of insulin analogs, biguanides, drugs with incretin effect — dipeptidyl peptidase‑4 inhibitors, agonists of glucagon-like peptide‑1, inhibitors of sodium-glucose cotransporter 2 diabetes. Particular attention is paid to the development of hepatocellular insufficiency and portal hypertension in patients with cirrhosis and type 2 diabetes, as well as processes for their prevention and insulin alternative correction methods.